APA style simplified : writing in psychology, education, nursing, and sociology - Beins, Bernard (Malden, MA : Wiley-Blackwell, 2012)
"This is a compact but comprehensive guide to writing clearly and effectively in APA style. Demonstrates how to write objective scientific research papers using interesting prose Incorporates guidelines from the 6th edition of the APA publication manual Explores how to develop ideas, connect them to what others have written, and express them clearly Discusses the differences between written, oral, and poster presentations and offers instructions for applying APA style to each"--
"In APA Style Simplified, experienced teacher and writer Bernard C. Beins guides young scholars through the labyrinth of APA style. He highlights the major elements of APA style and shows how to generate a coherent manuscript. Beins also explores how to develop ideas, connect them to what others have written, and express them in a style that reflects a sophisticated knowledge of the subject area. In addition, he features a sample manuscript showing common deviations from APA style, and how to correct these problems. An essential resource for those working on research papers, dissertations, and manuscripts within relevant subject areas, APA Style Simplified is a compact but comprehensive guide to writing clearly and effectively"--
Includes bibliographical references and indexes.
Includes bibliographical references and index.
Keywords: Psychology -- Authorship; Psychology -- Authorship -- Style manuals; Social sciences -- Authorship -- Style manuals; PSYCHOLOGY / General